Increasing stability of electric centrifugal pumps in submersible electromotor to voltage sags with adaptive undervoltage protection - Fedor Alexeyevich Losev; Valery Valentinovich Sushkov; Vadim Vladimirovich Timoshkin; Anton Sergeyevich Martyanov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2018)
Relevance. The considerable part of the mechanized oil production is carried out with electric centrifugal pumps. The submersible induction electromotor is the main part of the pumps. It has low resistance to short interruptions of power supply. The setting of the undervoltage protection is applied to decrease influence of the interruptions. The actuating characteristics have the given form and do not consider operating conditions of the submersible electromotor. The change in operating conditions of the submersible electromotor results in a shift of dynamic stability curve and the area between this curve and the actuating characteristic of the undervoltage protection occurs that leads to unreasonable shutdowns of electric centrifugal pumps. It is necessary to develop the adaptive undervoltage protection of the submersible induction electromotor for decreasing a number of such shutdowns. The main aim of the research is to increase submersible induction electromotor stability by development of the adaptive undervoltage protection Objects of the research are undervoltage protection and submersible induction electromotor. Methods: mathematical simulation on the basis of Park-Gorev equations for submersible induction electromotor; imitating modeling of the adaptive undervoltage protection including artificial neural network in a software package Matlab Simulink. Results. The authors have developed a simulation model of the submersible electromotor adaptive undervoltage protection on the basis of an artificial neural network; the undervoltage protection with the adaptive actuating characteristic for the submersible induction electromotor was simulated. The approximation of the actuating characteristic of undervoltage protection to dynamic stability curve will allow increasing a stability reserve on voltage to 12 %.